Struktur Sosial Kesultanan Palembang Darussalam Periode 1600–1825 - Metrahultikultura Metrahultikultura; Ahmad Falah (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2023)
The Palembang Darussalam Sultanate was one of the most important political and cultural powers in Sumatra from the seventeenth to the early nineteenth century. This study aims to analyze the social structure of the Palembang Darussalam Sultanate during the period 1600–1825 and the roles of each social stratum in sustaining the stability of sultanate rule. The research employs a historical method with a qualitative approach, encompassing the stages of heuristics, source criticism, interpretation, and historiography. Data sources were obtained from historical manuscripts, colonial archives, and relevant scholarly literature. The results indicate that the social structure of the Palembang Darussalam Sultanate was divided into several main strata, namely the sultan and the royal family, nobles and customary officials, ulama (religious scholars), merchants, and common people. The sultan held the highest authority, both political and symbolic, while nobles and customary officials played roles in governmental administration. The ulama exerted significant influence in religious life and the legitimation of power, whereas merchants served as the main drivers of the sultanate’s economy through regional and international trade activities. Common people occupied the lowest stratum, functioning as farmers, fishermen, and laborers. This social structure reflects a synthesis of traditional Malay systems and strong Islamic influences in the social and political life of the sultanate.